Pengaruh Pembelajaran Berdiferensiasi pada Mata Pelajaran IPAS Terhadap Hasil Belajar Siswa - Wardah Wardah; Lukman Hakim; Budi Utomo (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This study aims to determine the effect of differentiated instruction on student learning outcomes in the subject of Natural and Social Sciences (IPAS) for Grade IV at SD Negeri 247 Palembang. The background of this research is based on the low student achievement in the topic "Me and My Needs" and the suboptimal application of instructional strategies that address individual differences. Differentiated instruction is an approach that adapts the process, content, and product of learning based on students’ readiness, interests, and learning profiles. This study used a quantitative method with a quasi-experimental design, specifically the Nonequivalent Control Group Design. The sample consisted of 60 students selected through simple random sampling and divided into two groups: the experimental class (using differentiated instruction) and the control class (using conventional instruction). Data were collected through validated pretest and posttest essay-type questions. Data analysis was conducted using normality tests, homogeneity tests, and an Independent Sample T-Test with the help of SPSS version 26. The results showed that the average score of students in the experimental class increased from 40.67 to 71.27, while in the control class it increased from 28.8 to 55.00. The t-test showed a significance value of 0.001 < 0.05, indicating a significant difference between the two groups. Thus, it can be concluded that differentiated instruction has a positive and significant effect on student learning outcomes. This study recommends that teachers implement more differentiated instruction strategies to improve the quality of learning in elementary schools.